Optimalisasi Pengelolaan Zakat, Infaq, dan Sedekah Berbasis Nilai Spiritual Ramadan: Upaya Penanggulangan Kemiskinan dan Stunting di Kelurahan Lompoe Kota Parepare - Muhammad Nur Maallah; Amiruddin Z. Nur; Syahnur Rahman (LPPM Universitas Wijaya Putra, 2026)
This community service activity aims to enhance the management capacity of Zakat, Infaq, and Sadaqah (ZIS) based on Ramadan spiritual values as a strategy for Muslim family economic empowerment and poverty-stunting alleviation in Lompoe Village, Parepare City. Partner problems include: (1) low muzakki awareness in structured ZIS fulfillment; (2) weak managerial capacity of mosque administrators; (3) high rates of poverty (27.4%) and stunting (23.1%); and (4) suboptimal use of ZIS funds for productive programs. The implementation used Community-Based Participatory Action Research (CBPAR) over 6 months (July–December 2025), involving 85 active participants. Results showed significant improvements: ZIS collection increased by 41.2%; managerial capacity improved by 67.3%; beneficiary family income rose by an average of IDR 385,000/month; and stunting prevalence dropped by 16.8% within 6 months. The program successfully established an independent Mosque ZIS Management Institution (LPZM).